Development of Interactive Teaching Materials using The Flip Pdf Corporate Edition Application in Mathematics Learning in Grade IV of Elementary Schools - Eldi Fajri N; Ismira Ismira; Rahmatul Hayati (Journal of Educational Sciences, 2026)
This research is motivated by the low use of interactive learning media in Mathematics learning and the limited teaching materials that can facilitate students to learn independently and interestingly. The purpose of this research is to produce interactive teaching materials based on the Flip PDF Corporate Edition application for Mathematics learning for grade IV elementary school that are valid, practical, and effective, and to determine the level of validity, practicality, and effectiveness of the teaching materials developed. This type of research is a development research (R&D) using the ADDIE model. Expert validators are 3 experts (media experts, material experts, and language experts), 3 teachers, and grade IV students at SDN 06 Cimparuh and SDN 16 Cimparuh. The validation results show a validity level of 93.75% from media experts, 88.63% from material experts, and 90.6% from language experts, all of which are included in the "very valid" category. Based on the results of teacher and student responses, it is known that the percentage of practicality of teaching materials at SDN 06 Cimparuh reached 92.15% student responses and 95.8% teacher responses, while at SDN 16 Cimparuh 95.35% student responses and 91.6% teacher responses. In addition, the results of the effectiveness test showed an N-Gain value of 0.8054 at SDN 06 Cimparuh and 0.7825 at SDN 16 Cimparuh, including the high category. Thus, it can be concluded that interactive teaching materials based on Flip PDF Corporate Edition are valid, practical, and effective for use in learning Mathematics for grade IV elementary school.